Dragons. Defenders of Berk. Part 2 / [videorecording (DVD)] - Ferrera, America, 1984-; Baruchel, Jay, 1982- (distributed by Twentieth Century Fox, 2014)
Join Hiccup and his brave Viking friends as they battle surprising new enemies in ten fun-filled animated adventures based on the hit movie How to Train Your Dragon.